Pengaruh Strategi Pembelajaran Active Learning terhadap Peningkatan Motivasi Belajar Siswa - Eryani Rosmawati Nurhakim; Hamda Abdillah; Gusmaneli Gusmaneli (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to analyze the effect of the active learning strategy on improving students’ learning motivation. The background of this research is based on the low level of students’ learning motivation due to the dominance of conventional teaching methods that do not actively engage students. The research method used is a quantitative approach with an experimental design. The subjects of this study consist of students divided into an experimental class that implements the active learning strategy and a control class that uses conventional teaching methods. Data collection techniques were carried out through learning motivation questionnaires and observation of students’ activities during the learning process. The results show that there is a significant increase in learning motivation among students who participate in learning using the active learning strategy compared to those in the control class. Therefore, the active learning strategy has a positive effect on improving students’ learning motivation.